Propuesta de introducción de nuevos objetivos estratégicos en el proyecto plan integral de marketing turístico del Ministerio de Turismo del Ecuador para ampliar la visión de marca País-Ecuador a través de los principios de comunicación corporativa. - Vivero Sánchez, Michelle Stephanie (2010)
The current study shows a detailed investigation of the “PLAN INTEGRAL DE MARKTING TURISTICO EN EL ECUADOR” as well as one of its major accomplishments “MARCA PAIS DE ECUADOR” We studied the brands in our society, their evolution and how they reach to be the identification of a country, how it influences international relationships and how the good management of the brand can be a positive tool to administer the eventual problems of a country. MARCA PAIS was analyzed since an objective perspective, its beginnings, history, actors (MINISTERIO DE TURISMO), accomplishments, benefits and the importance that it represents in a globalize world; all this taking into account the principles of Corporate Communication. It was very important to check all the basic concepts such as the process of communication, corporate image, corporate identity, etc. So we can give the research a technical knowledge that will apply in the countries environment. The investigation was reinforce through the execution of the right instruments of research (interviews, etc.) which made possible the perception of a reality through tabulation and analysis. The foundation of this research was to be strategic, analytical and constructive; all this applying all the knowledge that was learn during the career.